(untitled) (Albayan Scientific Journal, 2023)
This experiment was conducted to test the efficiency of Alsol on the artificial ripening of green banana fruits, a local variety in Derna city. The treatments consisted of four concentrations of the substance (0, 500, 1000, 1500) ppm, and they were stored at room ambient temperature (16±2) and relative humidity (55%) The experiment was designed on the basis of a complete random design (CRD), and the results obtained showed that treatment with the substance of Alsol has a significant effect on the coloration of the peel of the fruits, and the ratio of the peel to the pulp. It has a significant effect on weight loss, which was increased with extending the storage period an result of increasin respiration rate and consumption of stored materials . The results also revealed that the substance of Alsol maintained the firmness of the fruits, and a slight increase in the percentage of total soluble solids, and this is one of the most important criteria for measuring the quality and degree of maturity of banana fruits